Simplifying Social Science : Research Proposal and Methods - Karubi, Nwanesi Peter (UNIMAS Publisher, 2020)
Working on this book was very tasking, but that is because I want to simplify the act of writing or designing the social science research methods and proposal for students and researchers alike. Thus, it came in a very small package for easy reading and comprehension. A research proposal explicitly explains what the researcher will investigate, why its important, and how you will do the research. Although, the format of a research proposal varies between fields, there are some common headlings. This book discuessed, illustrate and provide local examples on how to write these common headings. Hence, this book provides clarification on: What is social science research methods and why it is absolutely essential? How to write research aims? What is problem statement and how to write a concise one? How is a research objective generated from research question? What is the role of research objective in research? How to enter the field and collect quality data? How to exist the field and objectively analyze one's data?